Eucalypts, insects and birds: on the relationship between foliar nutrients and species richness - Majer, Jonathan; Recher, H. F.; Ganesh, S. (1996)
Using chemical knockdown procedures, canopy arthropod communities on eucalypts (Eucalyptus spp.) were found to be extraordinarily rich in species. Four seasonal samples from four species of eucalypts, two in eastern Australia and two in Western Australia, yielded 976 species of canopy arthropods from the eastern site and 683 species from the west. The richest and most abundant faunas occurred on the site with the greatest soil fertility and on the tree species with highest levels of foliage nutrients (i.e. nitrogen and phosphorous). High nutrient concentrations are taken as a measure of overall productivity. Seasonal and annual differences in arthropod abundances, biomass, and species richness are correlated with temporal changes in rainfall affecting tree phenological events (e.g. growth of new leaves) and productivity. Species of insectivorous birds that are dependent on energy-rich source carbohydrates (e.g. lerp, manna) select between plant species as foraging substrates on the basis of the kinds of arthropods available and their abundance on each kind of plant.